Current status and the significance of local wisdom biofertilizer in enhancing soil health and crop productivity for sustainable agriculture: A systematic literature review - Irwandhi, Irwandhi; Khumairah, Fiqriah Hanum; Sofyan, Emma Trinurani; Kamaluddin, Nadia Nuraniya; Nurbaity, Anne; Herdiyantoro, Diyan; Simarmata, Tualar (Kultivasi, 2024)
Soil fertility is recognized as a crucial factor in supporting plant growth and productivity. The utilization of biofertilizers as environmentally friendly fertilizers is aimed at enhancing soil fertility and plant productivity. This study aims to explore the potential of local material for developing local wisdom biofertilizers (LWB) for achieving sustainable agriculture. A systematic literature review was conducted using bibliometric analysis, Preferred Reporting Items for Systematic Reviews, and Meta-Analyses (PRISMA) method, employing the Scopus search engine with the keywords "local AND wisdom AND biofertilizer" OR "biofertilizer" OR "local AND microorganism" OR "soil AND health OR crop AND productivity OR sustainable agriculture". The search yielded 704 articles, of which 11 were deemed eligible after selection. Based on the literature review, it was found that there are local materials, including fish waste, seaweed, Azolla, fruit waste, Moringa oleifera, microalga, bamboo roots, banana hump, golden snail, mangrove leaves, fruit, and vegetable waste that can be used as raw materials for LWB to improve soil health, plant growth, and productivity. The development of LWB as a new fertilizer technology faces challenges such as lack of regulations, low public trust, limited farmer awareness, weak promotion, and raw material shortages. Further research is needed to intensively study and enhance the effectiveness of LWB through enrichment using beneficial microorganisms.